2004
DOI: 10.1002/jbm.a.30009
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐coated poly(L‐lactic acid) fibers provide a substrate for differentiation of human skeletal muscle cells

Abstract: Tissue engineering represents a potential method for repairing damaged skeletal muscle tissue. Extracellular matrix (ECM) proteins were evaluated for their ability to aid in cell attachment, whereas a poly(L-lactic acid) (PLLA) fiber scaffold was tested as a substrate for the differentiation of human skeletal muscle cells. In comparison to uncoated or gelatin-coated PLLA films, cell attachment increased significantly (p < 0.001) on PLLA films coated with ECM gel, fibronectin, or laminin. Myoblasts differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 20 publications
4
54
0
Order By: Relevance
“…4,7,8 Hence, promising results are shown by studies employing microfibrous scaffolds, which succeeded in driving myofiber development and orientation along the preferential direction of the scaffold fibers. 5,9,10 In agreement with these works, we previously demonstrated that DegraPol 1 , a block polyesterurethane, processed in the form of microfibrous meshes, provides a substrate for myoblast cell lines (C2C12 and L6) and primary human satellite cell adhesion and proliferation. 11 The study here attempted to deepen the investigation of skeletal myoblast behavior on DegraPol 1 membranes, in terms of adhesion, proliferation, and differentiation into multinucleated myotubes expressing myogenic markers.…”
Section: Introductionmentioning
confidence: 50%
“…4,7,8 Hence, promising results are shown by studies employing microfibrous scaffolds, which succeeded in driving myofiber development and orientation along the preferential direction of the scaffold fibers. 5,9,10 In agreement with these works, we previously demonstrated that DegraPol 1 , a block polyesterurethane, processed in the form of microfibrous meshes, provides a substrate for myoblast cell lines (C2C12 and L6) and primary human satellite cell adhesion and proliferation. 11 The study here attempted to deepen the investigation of skeletal myoblast behavior on DegraPol 1 membranes, in terms of adhesion, proliferation, and differentiation into multinucleated myotubes expressing myogenic markers.…”
Section: Introductionmentioning
confidence: 50%
“…Figure 1a outlines the two-step fabrication of the biosynthetic cell culture platform: 1) wet-spinning of the biodegradable fibers onto a substrate and 2) electrochemical modification of the substrate with a conducting polymer. The widely used biodegradable poly(DLlactic-co-glycolic acid) co-polymers (PLA:PLGA) were selected on the basis of their compatibility with numerous cell types, [6] including muscle [13] and for their extensive application in tissue engineering. [14] The selected co-polymer formulations were fashioned into fibers using our wet-spinning system, [15] similar to the spinning method reported previously by Nelson et al [16] Briefly, a PLA:PLGA co-polymer formulation in chloroform was carefully injected into a 1.5-cm diameter tube filled with isopropanol.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To overcome this problem, several approaches have been developed, such as integrating growth factors, or other bioactive agents into the polymer structure. 3,4 Another potential strategy to functionalize polylactide scaffolds could be the application of conductive polymers as a functional surface coating. Among these conductive polymers, polypyrrole (PPy) has emerged as a promising polymer group for tissue engineering due to its high biocompatibility and its good electroconductive properties.…”
mentioning
confidence: 99%